FAKTOR YANG MEMPENGARUHI KEPUTUSAN PELAKU UMKM BERGABUNG DENGAN RUMAH KREATIF BUMN GUNUNG SITOLI - Perlindungan Faebuadodo Hulu (Universitas Quality, 2021)
The ability to make effective decisions is a basic requirement, both for professional success and for the personal goals of MSME actors or consumers. Effective decisions are expected to produce expected and desired conditions. In decision making, there is a direct relationship between the number of discussions that were taken before the decision was taken and the participants involved in the discussion. The purpose of this study is to determine the influence of individual internal factors on the decision of MSME actors to join the Gunungsitoli BUMN Creative House. The type of research used is quantitative research which is the values of changes that can be expressed in numbers (scoring). This research is processed by regression analysis which is an analytical method that can be used to analyze data and draw conclusions about the independent variable (X) and the dependent variable (Y). From the calculation of the correlation coefficient, the results show that individual internal factor variables (X) have a positive effect on the decision of MSME actors (Y) to join the Gunungsitoli BUMN Creative House. This is evidenced from the results of the acquisition of a correlation value that is greater than the ttable value and a significance probability value of 0.000 <0.05, and has a moderate degree of correlation. Individual internal factor variables (X) have an influence on the decision of MSME actors (Y) to join Gunungsitoli SOE Creative House. This is evidenced from the results of the acquisition of a tcount value which is greater than the ttable value and a significance probability value of 0.000 <0.05, meaning that it partially has a positive and significant effect on the decision of MSME actors to join the Gunungsitoli BUMN Creative House. From these results it can be concluded that the importance of understanding individual internal factors for MSME actors and managers of the Gunungsitoli BUMN Creative House for decisions in using the products/services offered.